A computational fluid dynamics study of the effects of buoyancy on air flow surrounding a building. (May 2016) - Yau, YH; Lian, YC
In designing a durable building envelope, the air flow around a building plays an important role. Buoyancy is one of the factors that can affect air flow patterns. The contribution of outdoor buoyancy to the air flow surrounding a building was studied in this research. The building studied was the headquarters of the Malaysian Energy Commission. This building has a unique architectural outlook, and is called the Diamond Building due to its design. Outdoor field data such as air velocity, ambient temperature and surface temperature were collected during physical measurement. Air flow simulation was then carried out using the computational fluid dynamics software ANSYS. A total of four cases were studied in this research. Qualitative and quantitative analyses of the simulation results were carried out to show the influence of the outdoor buoyancy effect on the air flow patterns. The results showed that the air flow surrounding a building had a maximum velocity of 0.69 m/s dominated by the buoyancy effect when no wind was present. If a stronger natural wind of 3 m/s was present, the buoyancy effect was negligible. Practical application: The new findings from the outdoor buoyancy to the air flow surrounding a building in the tropics could be used as an important guide for building design engineers and researchers. The intention is to improve the design of building envelopes. Surrounding air flow has a significant influence on the building's ventilation as well as the outdoor contaminant movement, and it penetrates the building's envelopes. Surrounding airflow, which was considered solely contributed by wind previously, can now be examined at a more accurate airflow pattern by considering the buoyancy effect on airflow.